A SMIL-Based Approach for Designing Interactive Multimedia Film Players - Markus Tanubrata; Marvin Chandra Wijaya; Zulisman Maksom; Andrew Sebastian Lehman; Semuil Tjiharjadi; Agnes Hardiani Siahaan (SMATIKA JURNAL : STIKI Informatika Jurnal, 2026)
Typically, an HTML-style application requires extensive scripting to coordinate user interactions, manage display layout, and synchronize the timing of all interaction events. With Synchronized Multimedia Integration Language (SMIL), an alternative approach to developing an interactive multimedia film application has been defined, supporting time-based multimedia cooperation and user interactivity without the need for complex scripts. This study presents the development and evaluation of an SMIL-based interactive multimedia film application. The application allows for user-selected films to be automatically selected, played, and managed (synchronized) through an interactive GUI. The two measures, the Layout Consistency Score (LCS) and Screen Utilization Efficiency (SUE), were evaluated. Experimental evaluations have shown that the average LCS for the application = 0.92, indicating that the application maintains a consistent and predictable layout across multiple instances of the interface. In addition, the average SUE score for the application was calculated to be 0.79, indicating that it uses the available screen space efficiently and does not create a visually competing cluster. These results reinforce the concept that the region-based approach of SMIL and its declarative style for creating applications enable the development of multimedia that is consistently and efficiently presented across multiple contexts. As a result, the findings of this study indicate that the SMIL approach will simplify and allow for a practical methodology to build interactive multimedia film player applications, while preserving layout quality and interactivity.